320 Charlson comorbidity index as a factor impacting survival among ovarian cancer patients – results from a systematic review. (4th December 2020) - Asthana, Smita; Modi, Rahul
Abstract : Introduction/Background: There are a few scattered primary level studies from various regions of the globe proving impact of co-morbidities on survival in ovarian cancer patients. In last 20 years, there has been improvement in survival among ovarian cancer patients. Radical surgical approaches and advancements in chemotherapeutic agents have primarily contributed for same. Pre-existing uncontrolled co-morbidities impact ovarian cancer survival directly and indirectly. This affects the performance status of the patient leading to delay in treatment or aversion from radical surgical approaches thereby not achieving the goal of optimal treatment. It may also lead to a less aggressive chemotherapeutic modifications of using lower doses or single agent chemotherapy. The objective of this study was to systematically review the literature and summarize prevalence of various comorbidities with evaluation of impact of the Charlson Co-morbidity Index (CCI) on survival in ovarian cancer patients. Methodology: Primary studies were identified by following a defined search strategy on the prevalence of co-morbidity and survival pattern among ovarian cancer patients. This study has been conducted in accordance with PRISMA guidelines for systematic review. Co-morbidity assessment in the included studies had been done through the Charlson Co-morbidity Index (CCI) tool. Qualitative summarization of data from included studies for prevalence of various co-morbidities and influence of CCI score on survival in ovarian cancer patients has been performed. Results: Common co-morbidities prevalent in ovarian cancer patients were hypertension (11% to 26%), cardio vascular disease (4.5% to 12%) and diabetes (2.5% to 8.3%). Less commonly occurring co-morbidities were liver disease, renal disease, neurological problems and collagen vascular disease. Majority of ovarian cancer patients lie in CCI score 0 (68% - 76%). The range for one year% survival for CCI score 0 was 73 to 80%, for CCI score 1–2 : 58 to 71% and CCI score 2+ : 43 to 53%. The range five year% survival for CCI score 0 was 37 to 43%, for CCI score 1–2 : 24 to 30% and CCI score 2+ : 12 to 23%. Conclusion: Co-morbidities plays an important role in survival outcomes among ovarian cancer patients. Overall one year% and five year% survival decreases with increase in the CCI index score. Disclosures: The authors have no conflict of interest.